Advances in geophysical research. (Pergamon Press, 1991)
Advances in Geophysical Research, Vol. 2 introduces the theoretical and applied research on geophysics and seismology, earthquake prediction, and instrumentation in China. This book discusses the frictional resistance of fault slip; analysis of hypocenter location capability of a regional seismic network; and experimental study of electromagnetic emission during rock fracture. The possible triggering mechanism for a type of earthquake swarms; geographical distribution of the gravitational oceanic tidal load on the BTTZ area and mainland, China; and isostasy and crustal structure of Panzhihua-Xiehang Region in Southwestern China are also deliberated. This text likewise covers model 763 long-period seismograph and earthquake prediction research. This publication is a good reference for students and researchers aiming to acquire knowledge on the geophysics and seismology in China.